School Health Nursing in Promoting Healthy Eating Habits: A Review - Anita Acharya; Binita Acharya (Journal of Ayurveda Campus, 2025)
Background: Poor eating habits among school-aged children are linked to malnutrition, obesity, and non-communicable diseases. School health nursing plays a crucial role in health promotion, including fostering healthy eating behaviors. This review aims to synthesize available evidence on the effectiveness of school health nursing interventions in promoting healthy eating habits among school-aged children. Materials and Methods: A narrative review was conducted by searching PubMed, Scopus, CINAHL, and Google Scholar for studies published in different journal. Results and Discussions: Evidence suggests that school health nurses significantly improve children’s nutritional knowledge, increase fruit and vegetable intake, and reduce the consumption of unhealthy snacks and sugary drinks. Effective interventions included health education sessions, school-based screenings, mid-day meals, parent–teacher collaboration, and creation of supportive food environments. However, limited staffing, socio-cultural food practices, and exposure to unhealthy marketing remain barriers. Conclusion: School health nursing is effective in promoting healthy eating habits, but sustained success requires supportive policies, community engagement, and adequate resources.